2005
DOI: 10.1002/cncr.21167
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine plus oxaliplatin for the first‐line treatment of elderly patients with metastatic colorectal carcinoma

Abstract: BACKGROUNDIn patients with metastatic colorectal carcinoma (MCC), capecitabine has demonstrated a superior response rate (RR), equivalent disease progression‐free (PFS) and overall survival (OS), and an improved overall tolerability profile compared with bolus 5‐fluorouracil/leucovorin (5‐FU/LV). The FOLFOX4 regimen, combining oxaliplatin with LV and bolus plus infusional 5‐FU (LV5FU2), has been shown to improve RR and PFS versus LV5FU2, and it was more effective and less toxic than irinotecan plus bolus 5‐FU/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 45 publications
2
21
1
1
Order By: Relevance
“…However, given that the development of this toxicity depends on the total accumulated dose of oxaliplatin received during treatment, the low toxicity in our series can probably be attributed to the reduced number of treatment cycles received by our patients compared to the series of Cassidy et al (2004) (median 4.5 vs 8 cycles, respectively). On the other hand, the proportion of the elderly in our study that developed grade 3/4 adverse events was similar to the 29% reported in another study performed exclusively in the elderly and which also used a capecitabine/oxaliplatin regimen, in which the dose of subsequent cycles was increased as a function of tolerability by the patient (Comella et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, given that the development of this toxicity depends on the total accumulated dose of oxaliplatin received during treatment, the low toxicity in our series can probably be attributed to the reduced number of treatment cycles received by our patients compared to the series of Cassidy et al (2004) (median 4.5 vs 8 cycles, respectively). On the other hand, the proportion of the elderly in our study that developed grade 3/4 adverse events was similar to the 29% reported in another study performed exclusively in the elderly and which also used a capecitabine/oxaliplatin regimen, in which the dose of subsequent cycles was increased as a function of tolerability by the patient (Comella et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, median overall survival in our series was 13.2 months, which is somewhat less than the 17 -20 months reached in these other studies (Borner et al, 2002a;Zeuli et al, 2003;Cassidy et al, 2004). However, median overall survival was similar to that obtained in studies performed exclusively in the elderly with MCRC who received combinations of 5-FU/LV plus oxaliplatin or irinotecan (Aparicio et al, 2003), or capecitabine plus oxaliplatin (Comella et al, 2005). It has been noted that the survival of patients with MCRC increases when they receive three active cytostatic agents (5-FU/LV, oxaliplatin, and irinotecan) during their disease course (Grothey et al, 2004;Tournigand et al, 2004).…”
Section: Discussioncontrasting
confidence: 47%
“…Recently, more attention has been paid to combination chemotherapy of CRC with the regimen of capecitabine and oxaliplatin for safe, reliable and convenient medication. In certain randomized studies it was concluded that XELOX is non-inferior in terms of efficacy to the FOLFOX regimen in the first-line treatment of MCRC (5)(6)(7)9,11 Regarding adverse reactions during treatment, 5% of patients had Grade ≥3 hematologic toxicity, 8% of patients had Grade 3 peripheral neuropathy and 13% of patients had severe hand-foot syndrome (19). Similar results were obtained in another phase II trial that included a total of 50 patients aged ﹥70 years with MCRC, using the XELOX regimen as first-line therapy.…”
Section: Study (Year Reference) Pfs (Month) Median Os (Month) ------mentioning
confidence: 99%
“…Since general surgeons often perform chemotherapy in Japan, they are quite accustomed to the use of oxaliplatin. Therefore Japanese oncologists including gastrointestinal and general surgeons can often perform chemotherapy for elderly patients with oxaliplatin based regimens 1) .…”
Section: Introductionmentioning
confidence: 99%